INFORMATION SYSTEM DESIGN IN THE YAMAHA MUSIC SCHOOL - Pedi Gunardi; Drs. H. Soetirto Sadikin, M. A. Drs. H. Soetirto Sadikin, M. A. (Jurnal Sistem Informasi, 1997)
The design of Information Systems was written because this now requires speed and accuracy of the information needed by someone to assist their daily work. In this thesis, the writer tries to design a system to manage the company to facilitate the work performed by regular employees, both in terms of administration, education, until the preparation of reports to the CEO. In this system, also described the differences between the old system with a new system so it can be seen how quickly the new system.